The Relationship Between Secure Attachment Style and Self-Disclosure in Late Adolescents - Syiefa Atharida Pertiwi; Denrich Suryadi (Journal of General Education and Humanities, 2026)
This study examines the relationship between secure attachment style and self-disclosure among late adolescents in Jakarta, Indonesia (N = 170). The findings indicate a statistically significant yet weak positive correlation between the two variables (r(168) = .151, p = .050). This suggests that higher levels of secure attachment tend to be associated with increased self-disclosure; however, the magnitude of this association is limited and does not consistently reach a high level of openness. Conversely, lower levels of secure attachment do not necessarily correspond to lower self-disclosure, as the observed relationship is correlational rather than causal and may be influenced by other internal and external factors. Overall, secure attachment style is related to adolescents’ self-disclosure, but it should not be regarded as the sole determinant of openness during late adolescence.